Hard facts and envIRONmental impacts: An overview of the global iron and steel sector - Karin Küblböck; Bernhard Tröster; Michael Eigner (Austrian Foundation for Development Research (ÖFSE), 2022)
This briefing paper provides an overview of t he global iron and steel sector. It describes the properties of iron ore and delineates the geographical distribution of deposits and trade flows. Further, it explains pricing mechanisms and addresses environmental impacts. Iron and steel are key materials for industrial production, with iron being used 20 times more than all other metals combined. While extraction of iron ore has almost tripled over the past twenty years, the iron and steel sector remains highly concentrated, with most iron ore extraction taking place in just a few countries, in particular in Australia and Brazil, which account for over half of all iron ore extraction. Indeed, more than two-thirds of the iron ore export market is controlled by only four companies. In terms of global steel production, China accounts for more than half of the market share. Iron ore is also mined in Austria, and significant quantities are imported for steel production, although there is a lack of transparency; Austria is the only country in the EU not to publish statistical data on its iron ore imports since 2018. Globally, iron and steel represent the larges t sector in terms of energy demands, CO 2 emissions and air pollution and are among the world's major water consumers. Prices of iron ore are highly volatile, which has major consequences for exporting and importing countries and makes planning for CO2 phase-out difficult.
Keywords: 330; iron ore; steel; trade flows; price volatility; China; Austria